(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Several corona virus vaccines from different countries are currently available for usage. Aims: The aim of this survey is to report the vaccination approval of COVID-19 through the topography of Jordan and to recognize the most likely rationale of acceptance or refusal of COVID-19 vaccination. Materials and methods: In January 2021, a survey was distributed to several governorates in Jordan to reveal the acceptance of the Jordanian community to COVID-19 vaccination, and to find out the reasons behind their refusal to take the vaccine. Results: Of these, 29.6% study participants showed willingness to take the vaccine, while about 40.4% of the study participants showed unwillingness to get vaccinated. Most of the respondents were afraid from the side effects waiting for more scientific news or any instruction from government sources about the effectiveness and safety of the vaccines provided to the population. However, the behavior toward vaccination was encouraging, but anxiety and fear was a common factor with all the participants regardless of their culture, level of education or even their age. Conclusion: The acceptance of vaccination for COVID-19 turned out to be weak. Most of the respondents were afraid of the side effects, waiting for more scientific research from any governmental institution to instruct the population about effectiveness and safety of the vaccines. However, the behavior toward vaccination was encouraging, but anxiety and fear was a common factor with all participants regardless of their culture, level of education or even their age. The different elements powering people to accept or refuse the vaccine should be reported and emphasized to relevant institutions, to study and assist the common health and economic status of the community.